Women’s attitudes towards physical intimate partner violence in India: Trends, patterns, and determinants - Shreemoyee Shreemoyee; Punarjit Roychowdhury; Gaurav Dhamija (PLoS ONE, 2025)
Women’s attitudes towards physical intimate partner violence are a major determinant of the likelihood of their exposure to physical intimate partner violence. In this study, we scrutinize the third, fourth, and fifth rounds of the National Family Health Survey using descriptive analyses and logistic regression models to understand the trends, patterns, and drivers of women’s attitudes towards physical intimate partner violence across various demographic and socioeconomic groups in India. Our findings reveal a noticeable decline in the level of women’s acceptability of physical intimate partner violence over the past 15 years, albeit at a slow pace. Furthermore, the study demonstrates that the acceptability of physical intimate partner violence is more prevalent among women from demographically and socioeconomically disadvantaged backgrounds. This includes women who marry at a young age, have no formal education, are exposed to interparental violence, belong to lower caste or tribal communities, exhibit poor wealth status, and reside in rural areas. The findings suggest a need for targeted policy interventions focusing on enhancing educational opportunities and promoting socioeconomic equity, particularly within demographically and socioeconomically disadvantaged groups.